Characterization of a versatile glycoside hydrolase Cel5M from Pectobacterium carotovorum HG-49 for ramie degumming. Issue 13 (July 2020) - Wang, Yawei; Bai, Yun; Shu, Tong; Fan, Pei; Zhang, Huashan; Turunen, Ossi; Xiong, Hairong; Yu, Longjiang
A novel versatile glycoside hydrolase Cel5M was identified from Pectobacterium carotovorum and used in ramie degumming. The full-length Cel5M (GenBank: MH544226) containing the catalytic domain Cel5MD and its carbohydrate-binding module (CBM3) were expressed in E. coli . Both Cel5M and Cel5MD showed a broad substrate spectrum cleaving konjac glucomannan (KGM), carboxymethylcellulose (CMC) and oat spelt xylan. The optimal temperature of Cel5MD was 55 o C with CMC and KGM, whereas the optimum temperature of Cel5M was 65 o C with KGM and 60 o C with CMC. The improved thermal activity with KGM was probably reflected also in the much lower K m with KGM than with CMC, indicating stronger binding of the full-length enzyme with KGM. Both enzymes were highly stable over a broad pH range from pH 5.0 to 9.0 with KGM. The use of the Cel5M enzyme together with the wild-type P. carotovorum HG-49 strain showed significant improvement when compared to using the mere strain HG-49 for application in ramie degumming. Moreover, the whole P. carotovorum Cel5M gene was over-expressed in P. carotovorum HG-49 itself to improve the ramie-degumming capacity. Altogether, this study indicates that in situ production of processing enzymes could be utilized in the textile industry.